A study on vermicompost yield and total microbial count by Eudrilus Eugeniae species under different temperature regime - Kamaruddin M.A.; Idrus A.F.M.; Norashiddin F.A.; Ibrahim M.H.; Hamzah M.R.; Zawawi M.H.; Alrozi R. (American Institute of Physics Inc., 2023)
Fertilisers are widely used in agriculture to increase the yield of crops production. One of conventional ways in producing fertilizer is by vermicomposting which is considered as ecofriendly fertilizer in agriculture application. But, in terms of storage and transportation, it is difficult for farmers to ready with appropriate facilities owing to its high moisture content. The drying process was introduced to overcome this problem by studying the effects of microbial populations before and after the drying process. Samples were taken from the Pertubuhan Peladang Kawasan (PPK) Mada Sungai Dalam. Commercial vermicompost was used as a control sample were bought and raw vermicompost at the plot were taken for testing of drying at different temperatures. The drying process was done using Memmert UM100 oven at temperatures of 75C, 65C and 55C for 3 hours. From the study, the temperature at 75C showed the lowest reading of total microbial populations which is 49 104 CFU/mL while temperature at 65C and 55C shows 110 104 CFU/mL and 126 104 CFU/mL respectively. It can be concluded that, the higher the temperature applied on the vermicompost, the lower microbial population it contained due to loss of moisture content in vermicompost. The results demonstrated that although vermicompost could be dried, it has significant effect in terms of dwindling numbers of total microbial population. 2018 Author(s).